2023
DOI: 10.1039/d3nr02082g
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired magnetism-responsive hybrid microstructures with dynamic switching toward liquid droplet rolling states

Abstract: The functionality of tunable liquid droplet adhesion is crucial for many applications such as self-cleaning surfaces and water collectors. However, it is still a challenge to achieve real-time and fast...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…47 To obtain desired material qualities while reducing production costs, 48 ML algorithms may improve the manufacturing process of FRECs by altering factors such as curing time, temperature, and pressure. 49 ML speeds up creating new materials with superior performance characteristics for various applications, 50 including aerospace, automotive, biomedical, and beyond. 51 The literature review revealed that the woven mat composites exhibit very promising and improved mechanical properties compared to the nonwoven type.…”
Section: Introductionmentioning
confidence: 99%
“…47 To obtain desired material qualities while reducing production costs, 48 ML algorithms may improve the manufacturing process of FRECs by altering factors such as curing time, temperature, and pressure. 49 ML speeds up creating new materials with superior performance characteristics for various applications, 50 including aerospace, automotive, biomedical, and beyond. 51 The literature review revealed that the woven mat composites exhibit very promising and improved mechanical properties compared to the nonwoven type.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulating droplets on surfaces and interfaces is critical for the efficiency and tunability of water desalination, condensation, liquid transport in microfluidics, and digital bioassays . For example, condensation, a key process in power generation and thermal management, requires fast removal of droplets from the substrates for efficient heat transfer. , Passive methods to transport droplets on surfaces have focused on engineering asymmetric surface structures and gradient chemistry. However, these surfaces typically require complex fabrication and do not offer real-time control capability. Active methods that can dynamically tune droplet motions have been developed using electric, , magnetic, acoustic, chemical, , thermal, , and photothermal , stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al 44 examined the thermo-mechanical mechanism subject to soil particle re-arrangement of thermodynamics granular. Bian et al 45 , Zhu et al 46 and Zhang et al 47 respectively worked bioinspired magnetism-responsive hybrid microstructures, generalized micro-fluid rectifiers via anisotropic slippery hollow tracks and nonlinear hysteretic behaviours with strain-stiffening of magnetorheological gel composite applications. Attributes of cavity dynamics, trajectories and forces on vertical water entries, shear thickening fluids and behaviour between fluid and structure from coupling system respectively investigated by Lyu et al 48 , Sun et al 49 and Huang et al 50 .…”
Section: Introductionmentioning
confidence: 99%